(untitled) (Bangladesh Journal of Medical Science, 2024)
Objective The objective of the present study was to evaluate the antimicrobial effects of essential oils on fabrics and surgical gauze. Materials and methods The antimicrobial activity of essential oils of Anethum graveloens, Cinnamommum tamala, Citrus bergamia, Pelargonium graveolans, and Trachyspermum ammi was determined against Gram-positive & Gram-negative bacteria and a dermatophytic fungi. An antimicrobial evaluation was carried out by disc-diffusion, micro broth dilution, in-vitro dressing, and scanning electron micrographic methods. Percentage reduction of microorganisms and wash durability of essential oil treated fabric was also determined. Results and discussion The largest diameter of the inhibition zones was obtained against Bacillus subtilis by Trachyspermum ammi essential oil around the fabric disc. The value of MIC was, 0.031% v/v for Bacillus subtilis and both strains of Staphylococcus aureus, whereas MBC was determined to be 0.25% v/v and 0.5% v/v respectively. Sensory evaluation of the treated fabric and gauze revealed a gradual decline in odour intensity. The highest reduction in microbial counts has been observed in Trachyspermum ammi EO (0.125%) treated gauze disc both against Bacillus subtilis followed by Trichophyton rubrum. Conclusion High laundering durability, inhibition of microbial cells, and retention of EOs indicates the promising antimicrobial and aroma-therapeutic potential of Trachyspermum ammi and Cinnamommum tamala EOs in fabrics. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 775-786